“Pancreatic undifferentiated carcinoma with osteoclast-like giant cells (UC-OGC)” on cytology: two case reports on a variant of pancreatic adenocarcinoma - Sharma, Anjali; Jamil, Syeda Firdos; Mathur, Arpita; Singh, Chaitali (Indian Journal of Case Reports, 2020)
Undifferentiated carcinoma of the pancreas with osteoclast-like giant cells (UC-OGCs) is a rare entity, less than 1% of all pancreatic malignancies. Recent studies quoted that the prognosis of these cancers is more favorable and displays a less aggressive with slow metastasis and lymph node spread compare to patients with an associated conventional pancreatic ductal adenocarcinoma. Here, we describe a case series of two reports of undifferentiated carcinoma with OGCs of the pancreas in the duration of 10 years. Both the cases presented with complaints of abdominal pain and weight loss. Laboratory investigation revealed a normal level of amylase and lipase. One of the cases showed mild elevation of CA19-9. Endoscopic ultrasound-guided fine?needle aspiration was performed and diagnosis of undifferentiated carcinoma with OGCs of pancreas made on aspiration cytology and cell block. Due to the rarity of the tumor, there is a lack of prospective studies on treatment options. However, surgical en bloc is currently considered first-line treatment. The role of chemotherapy and radiotherapy has not been established.